Transferência do direito de construir como uma das formas de indenização do tombamento - Manzato, Maria Cristina Biazão (2007)
This work has the objective of analyses the development rights transfer as one of the forms of heritage rights compensation. This institute has an especial importance in the cultural heritage preservation, that it imposes restriction to the owner, with the purpose of keeping the original characteristics of the good, that justifies its preservation and, from these restrictions, can result some looses. The biggest problem that involves the heritage register is the compensation, that must be measured in view of the limitation occurrence to one of the contents of property rights and what is its financial repercussions. . The heritage registered of the good non-changed presents itself as a restriction that affects the development rights. As a way of compensation to the owne, by the fact he can t exercise the development rights in its totality, the institute of development rights transfer has been created and makes possible to the owner to use in another place or even alienate this right. The institute has been taken in the legal order, by the City Law, that disciplines the development rights transfer at its article 35, that integrates the general rules of the urban order, that can be implanted by all the Cities, that is included at the City Plan and specific law that establishes the application conditions. The instituted law of development rights transfer will must identify the goods declared as preservation interest; to indicate the areas that can receive the development potential; to measure or bring clearly how it will be estimated the value of development potential that can be transferred. It can be transferred the zoning bonus result from the difference between the used bonus and the basic zoning bonus; in that the development rights integrates the property right until this limit. If the only imposed restriction to the owner refers to the development rights, this right transfer will be able to redress him totally or even avoid the damage or reduce it and make it an important instrument of culture goods preservation, that consists itself in one of the solutions for the problem of heritage register compensation